Mechanical, durability and microstructural performance of Kenaf Fibre-Rreinforced Geopolymer Composites - Najm, Alghazali Noor Abbas (2022)
Ordinary Portland Cement (OPC) is the main ingredient in concrete, which is commonly used in construction applications because of its excellent mechanical and durability performances. However, concrete and cement-based products produce greenhouse gas emissions, which gives a bad impact on the environment. Hence the development of greener construction materials is in need. Recently, many researchers have focused on geopolymer materials, which improve the greenness of conventional concrete with comparable or better characteristics. Geopolymers have good mechanical properties, are non-flammable, acid-resistant, longlasting, and have fewer CO2 emissions than OPC. However, when subjected to flexure and tension stresses, the brittleness of geopolymer composites (GPC) is inherent. Therefore, natural fibres, kenaf is introduced to improve the brittleness, control crack propagation, and enhance flexural and tensile strength. This composite is abbreviated as Kenaf Fibre-Reinforced Geopolymer Concrete Composites (KFRGC) in this thesis. This research studied the KFRGC with kenaf fibre volume fractions of 0.75, 1.0, 1.25, and 1.5%, and fibre lengths of 20, 30, and 40mm. The fibres are mixed with 40 MPa geopolymer composite with fly ash (FA) and ground granulated blast slag (GGBS) as binders. A series of standard material tests were conducted to determine the impact of kenaf fibres on the fresh, mechanical, durability and microstructural properties of KFRGC. The results demonstrated that the workability and unit weight of KFRGC reduced as the fibre volume fraction and length increased. The inclusion of higher volume fractions and longer lengths of kenaf fibres did not improve the compressive strength and modulus of elasticity at all ages but give higher tensile strength and flexural strength. The KFRGC prepared with 1.25% fibre volume fraction (Vf) and 30 mm long obtained the highest tensile and flexural strength with an improvement of about 20% and 27%, respectively, compared to the plain geopolymer. This improvement was justified by the strong fibrematrix interfacial adhesion properties, which transferred a high amount of stress from the matrix to the fibre, as evidenced by the FESEM images. The specimens showed a triangular failure pattern with oblique cracks on brittle geopolymer without fibres, while retaining their original shape with a few vertical cracks and fissures on KFRGC samples. This shows that, although natural fibres have lower tensile strength than synthetic fibres, it is sufficient to alter the failure mode of GPC from brittle to ductile. In terms of durability, KFRGC showed that increasing the fibre length or volume will impact their performance. All durability and water resistance tests showed that longer and higher Vf of KF caused fibre balling during mixing and resulted in lower properties of KFRGC. In conclusion, the optimum kenaf fibre length and Vf recommended for KFRGC is 30 mm and 1.0%, respectively for use as indoor composite green materials. This research paves the way for kenaf addition in geopolymer concrete as a better option of a potential green material natural fibre than coconut, which has less tensile strength. This hopefully contributes to an option of green concrete in construction industries.